ANTISIPASI DINDING PENAHAN TANAH DAERAH PANGKALAN KM 16 KABUPATEN LIMA PULUH KOTA - Hanifah - Asnur (Jurnal Pembangunan Nagari, 2019)
The high intensity of rainfall in the Pangkalan area results in soil water content> 50% (watery or wet soil) so that the soil is at its saturation point and prone to landslides. The purpose of this study was to overcome the occurrence of landslides / slope collapse in the Pangkalan area, using the cantilevered retaining wall method. Soil samples were taken at base points 10, 16 and 20 using handboards. Laboratory tests are carried out to determine water content, atterberg limits, volume weight, specific gratify, filter analysis, direct share and UCST. The data is processed by analyzing the original soil water content, atterberg limit and variations in water content, and calculating the retaining wall using the cantilever method to obtain the value of the safety factor for rolling, shearing and safety factors for the carrying capacity of the soil. The results showed that the presence of a retaining wall can increase the value of the slope to rolling safety factor by 3.72, the safety factor for shear by 2.4, and the safety factor for carrying capacity by 34.89. Further research can also be carried out to anticipate retaining walls at base point 10, and base point 20. Keywords : Soil, Moisture content, Landslides, Cantilever Retaining Walls